Direct Displacement Based Design on Moment Resisting Frame with Out-of-plane Offset of Frame. (2015) - Muljati, Ima; Kusuma, Amelinda; Hindarto, Fonny
Abstract: Direct displacement based design (DDBD) has been widely applied in several structural systems including moment resisting frame (MRF), the most common type of structures used in design practices. Due to architectural demand, recently many buildings involving some out-of-plane offset of frames in MRF system. The existence of out-of-plane offset in frame system raises differences force distribution among frames compared with the regular one without the offset. This study will observe the effect of out-of-plane offset of frame in a concrete regular MRF designed using DDBD method for two different earthquake level. Nonlinear time history analysis is used to verify the structural performance based on three parameters: story drift, damage indices and structural failure mechanism. The offset frame is assumed to be in-plane with the adjacent frame, the existence of offset is ignored, and the structure is designed as a regular MRF. The study shows that the main structural problem arises from the beams at the offset area due to high shear demand. DDBD procedure enable to adjust the ductility demand of these beams in order to improve the structural performance without involving design repetition as usually done in traditional seismic resistant design. In conclusion, DDBD performed well in predicting the seismic demands of the MRF system with out-of-plane offset of frame. The existence of offset frames in MRF system can be ignored during the design process as long as the ductility demands of beams at the offset area is well adjusted.